Composition for charge generation layer and organic electroluminescent device comprising same
By using specific compositions in OLED devices to improve the π-π stacking situation between n-CGL and p-CGL layers, the problem of high electron injection barriers is solved and the driving voltage and power consumption are significantly reduced.
Patent Information
- Application Number
- CN202411448026.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
In OLED devices, the electron injection barrier between the n-type charge generation layer (n-CGL) and the p-type charge generation layer (p-CGL) is high, which affects the driving voltage and power consumption of the device, and the material stacking is poor. Causes poor interface contact.
Develop a composition for the charge-generated layer, including a specific general structure, and reduce the power injection barrier by improving the π-π stacking situation between the N-CGL and P-CGL layers.
The charge generation capability of the charge generation layer is significantly improved, the π-π stacking effect at the interface of the n-type and p-type charge generation layers is improved, the injection barrier and driving voltage are reduced, and the power consumption of the device is reduced.
Smart Images

Figure CN119343036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OLED, and specifically comprises a composition for a charge generation layer and an organic electroluminescent device comprising the composition. Background Art
[0002] In current OLED devices, the luminous brightness and device life can be significantly improved by using multiple light-emitting layers in series. To achieve light emission from multiple light-emitting layers, it is necessary to use n-type charge generation layer (n-CGL) material and p-type charge generation layer (p-CGL) material to connect the two light-emitting layers. When the device is working, under the action of the electric field, holes and electrons are separated in the p-CGL layer, and electrons are injected through the interface between the p-CGL layer and the n-CGL layer, and then transferred to the light-emitting layer through the electron transport layer. Studies have found that the electron injection barrier between the n-CGL material and the p-CGL material will significantly affect the device driving voltage, and thus affect the power consumption of the overall panel.
[0003] In the process of studying the electron injection barrier, it was found that the material injection barrier is not only affected by the energy levels of the two layers of materials, but also related to the stacking between the layers. Generally, the stacking form of molecules is π-π interaction, which is a specific form of intermolecular interaction and is related to the van der Waals interaction and electrostatic interaction between molecules. In OLED devices, the same structural material is used in the same layer, and the arrangement or stacking between materials is often better. However, at the interface where the two layers of materials are in contact, due to the difference in compound structure, the electron / hole injection barrier will be increased due to poor interface contact.
[0004] Therefore, in order to obtain better π-π stacking at the interface of the p-CGL layer and the n-CGL layer, it is urgent to develop a composite material that can be applied to the p-CGL layer and the n-CGL layer, respectively, to improve the stacking condition at the interface and the injection barrier of the material. Summary of the invention
[0005] In view of the above problems in the prior art, the present invention provides a composition for a charge generation layer.
[0006] To achieve the above objectives, the technical solutions adopted by the present invention include:
[0007] The first aspect of the present invention provides a composition for a charge generation layer, the composition comprising a general structure shown in Formula I and a general structure shown in Formula II:
[0008]
[0009] N(Ar1)(Ar2)(Ar3)II;
[0010] In Formula I,
[0011] R1 and R2 are the same or different, and are independently selected from any one of H, C1-C10 alkyl, and phenyl;
[0012] Ar is selected from one or more combinations of benzene, spirobifluorene, dibenzofluorene, dimethylfluorene, diphenylfluorene, biphenyl, terphenyl, and naphthalene;
[0013] In formula II,
[0014] Ar1 to Ar3 are the same or different, and each is independently selected from a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted C6-C30 heteroaryl group, and at least one of Ar1 to Ar3 is selected from a combination of one or more of benzene, spirobifluorene, benzophenone, dimethylfluorene, diphenylfluorene, biphenyl, terphenyl, and naphthalene.
[0015] At least one hydrogen in Formula I and Formula II may be replaced by deuterium, and at least one nitrogen may be replaced by nitrogen-15( 15 N) substituted, at least one oxygen may be replaced by oxygen-17( 17 O) or oxygen-18 ( 18 O) substituted, at least one carbon may be substituted by carbon-13 ( 13 C) Replacement.
[0016] Further, Ar is selected from one of the following structures:
[0017]
[0018]
[0019] Further, Ar1 to Ar3 are selected from one of the following structures:
[0020]
[0021] Further, R1 and R2 are each independently selected from any one of H, methyl and phenyl. Further, the formula I is selected from one of the following structures:
[0022]
[0023]
[0024]
[0025]
[0026] Further, the formula II is selected from one of the structures shown below:
[0027]
[0028]
[0029]
[0030] The second aspect of the present invention provides a use of the composition as described above in preparing an organic electroluminescent device.
[0031] The third aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more compositions as described above.
[0032] Furthermore, the charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more compounds of the structure shown in Formula I, and the p-type charge generation layer includes one or more compounds of the structure shown in Formula II.
[0033] A fourth aspect of the present invention provides a display or lighting device, which includes the organic electroluminescent device as described above.
[0034] Beneficial effects of the present invention:
[0035] The composition provided by the present invention not only has a high charge generation ability, but also can improve the stacking of materials at the interface. The composition provided by the present invention is applied to the n-type charge generation layer and the p-type charge generation layer of the organic electroluminescent device. The composition provided by the present invention can not only significantly improve the charge generation ability of the charge generation layer, but also can improve the π-π stacking effect at the interface between the n-type charge generation layer and the p-type charge generation layer, reduce the injection barrier of the n-type charge generation layer and the p-type charge generation layer and the driving voltage of the device, and overcome the defects of the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION
[0037] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.
[0038] The composition of the present invention is suitable for use in light-emitting elements, display panels and electronic devices, and is particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.
[0039] Experimental Section
[0040] In order to understand the content of the present invention more clearly, the composition, the preparation method of the composition and the luminescent characteristics of the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of an embodiment of the present invention. However, it should be noted that the synthetic method of the compound of an embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.
[0041] Synthesis Example 1
[0042]
[0043] A1 (6.1 g, 20 mmol), B1 (3.8 g, 10 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to finally obtain product C1: 4.7 g, yield: 70%, MS (m / z) (M+): 673.
[0044] Synthesis Example 2
[0045]
[0046] Using the same method as in Synthesis Example 1, A2 (7.6 g, 20 mmol) and B2 (3.9 g, 20 mmol) were used to replace A1 and B1, and finally product C2 was obtained: 5.7 g, yield: 69%, MS (m / z) (M+): 827.
[0047] Synthesis Example 3
[0048]
[0049] Using the same method as in Synthesis Example 1, A3 (6.1 g, 20 mmol) and B3 (2.7 g, 20 mmol) were used to replace A1 and B1, and finally product C3 was obtained: 3.4 g, yield: 61%, MS (m / z) (M+): 561.
[0050] Synthesis Example 4
[0051]
[0052] Using the same method as in Synthesis Example 1, A4 (6.4 g, 20 mmol) and B4 (2.6 g, 20 mmol) were used to replace A1 and B1, and finally product C4 was obtained: 4.4 g, yield: 76%, MS (m / z) (M+): 579.
[0053] Synthesis Example 5
[0054]
[0055] Using the same method as in Synthesis Example 1, A5 (6.1 g, 20 mmol) and B5 (2.6 g, 20 mmol) were used to replace A1 and B1, and finally product C5 was obtained: 3.9 g, yield: 71%, MS (m / z) (M+): 551.
[0056] Synthesis Example 6
[0057]
[0058] E1 (6.1 g, 20 mmol), F1 (5.6 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to finally obtain product G1: 5.7 g, yield: 75%, MS (m / z) (M+): 381.
[0059] G1 (6.1 g, 15 mmol), H1 (5.6 g, 15 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to finally obtain product I1: 6.1 g, yield: 68%, MS (m / z) (M+): 601.
[0060] Synthesis Example 7
[0061]
[0062] E2 (6.1 g, 20 mmol), F2 (4.8 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4: 1 (V / V), and then tetrakis triphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by column separation using petroleum ether: dichloromethane = 10: 1. Finally, the product G2: 4.8 g, yield: 71%, MS (m / z) (M+): 341 was obtained.
[0063] G2 (4.8 g, 14 mmol), H2 (5.2 g, 14 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to finally obtain product I2: 4.9 g, yield: 62%, MS (m / z) (M+): 561.
[0064] Synthesis Example 8
[0065]
[0066] E3 (6.1 g, 20 mmol), F3 (8.6 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified using a petroleum ether: dichloromethane = 10:1 (V / V) column to finally obtain product G3: 6.7 g, yield: 63%, MS (m / z) (M+): 529.
[0067] G3 (6.7 g, 13 mmol), H3 (4.8 g, 13 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 100 ml toluene: water = 4: 1 (V / V), and then tetrakis triphenylphosphine palladium (0.6 g, 0.5 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 10: 1 (V / V) column. Finally, the product I3 was obtained: 6.8 g, yield: 70%, MS (m / z) (M+): 749.
[0068] Synthesis Example 9
[0069]
[0070] J1 (7.5 g, 20 mmol), K1 (7.9 g, 20 mmol) and sodium tert-butoxide (2.9 g, 30 mol) were added to toluene (1000 mL), and then bis(dibenzylideneacetonepalladium) (0.56 g, 1 mmol) and BINAP (1.24 g, 2 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product L1: 9.0 g, yield: 65%, MS (m / z) (M+): 692.
[0071] Synthesis Example 10
[0072]
[0073] Using the same method as in Synthesis Example 9, J2 (8 g, 20 mmol) and K2 (6.2 g, 20 mmol) were used to replace J1 and K1, and the final product L2 was obtained: 9.9 g, yield: 79%, MS (m / z) (M+): 630.
[0074] Synthesis Example 11
[0075]
[0076] Using the same method as in Synthesis Example 9, J3 (7.2 g, 20 mmol) and K3 (10.2 g, 20 mmol) were used to replace J1 and K1, and the final product L3 was obtained: 8.9 g (yield: 56%), MS (m / z) (M+): 788.
[0077] Synthesis Example 12
[0078]
[0079] Using the same method as in Synthesis Example 9, J4 (13 g, 20 mmol) and K4 (6.4 g, 20 mmol) were used to replace J1 and K1, and the final product L4 was obtained: 11.9 g, yield: 67%, MS (m / z) (M+): 889.
[0080] Synthesis Example 13
[0081]
[0082] Using the same method as in Synthesis Example 9, J5 (8.4 g, 20 mmol) and K5 (7.9 g, 20 mmol) were used to replace J1 and K1, and the final product L5 was obtained: 9.1 g, yield: 62%, MS (m / z) (M+): 736.
[0083] Synthesis Example 14
[0084]
[0085] Using the same method as in Synthesis Example 9, J6 (7.2 g, 20 mmol) and K6 (7.9 g, 20 mmol) were used to replace J1 and K1, and the final product L6 was obtained: 7.8 g, yield: 58%, MS (m / z) (M+): 676.
[0086] Comparative Example 1-2
[0087]
[0088] Material performance evaluation
[0089] Using gromacs 2019.3 software, based on the GAFF force field and RESP atomic charge, a 10*10*10nm cubic box was constructed, and the compound combination of the device of the present invention was used for calculation. After that, a 100ps equilibrium MD simulation was performed under NVT to fully balance the system. Based on this system, a 5ns generative MD simulation was performed under 1atm and 298K external environment settings based on NPT with periodic boundary conditions. The last 2ns MD trajectory was divided into 20 parts to calculate the average distance and interaction energy between the compound combinations in the present invention.
[0090] The molecular structures used in MD simulations were obtained by Orca software, based on the density functional theory (DFT) calculation method (the basis set level was set to: b3lyp / 6-31G(d), the charge number was 0), and the molecular structures were subjected to geometric optimization and vibration analysis (Opt+freq). During the calculation, the structures used did not have imaginary frequencies.
[0091] Referring to the π-π stacking interaction between benzene molecules, the energy and intermolecular distance between n-CGL material and p-CGL material are calculated. The distance between the centers of mass (R) of n-CGL material and p-CGL material is changed, and the interaction energy E is calculated. The relationship curve between E and R is the potential energy surface of the interaction energy. The interaction energy and the center of mass distance at the minimum point on the potential energy surface curve are recorded as Ee and Re, respectively, which are the π-π stacking intensity and stacking distance of the material combination.
[0092] The results are shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] When the absolute value of Ee is larger or Re is smaller, it can be shown that the π-π stacking effect between materials is stronger. From the data in Table 1, it can be seen that the distance between the centers of mass of the composite provided by the present invention is smaller than that of the comparative composite, and the interaction energy is larger, indicating that the π-π stacking effect between the composite provided by the present invention is stronger.
[0097] In order to obtain efficient TOLED devices, the charge generation layer (CGL) plays an extremely important role. It not only connects the two light-emitting units, but more importantly, it generates charges and can effectively inject and transfer the generated charges into the light-emitting units.
[0098] In order to illustrate that the composition provided by the present invention has good charge generation ability, the compositions provided by Synthesis Examples 1 to 14, Comparative Example 1 and Comparative Example 2 of the present invention are respectively applied to devices as charge generation layer materials, and the charge generation ability of the charge generation layer material is measured by measuring the current density of the device.
[0099] Experimental device 1
[0100] The structure of the experimental device of the present invention is as follows: indium tin oxide (ITO) / p-dopant (thickness 5nm) / NPB (thickness 35nm) / charge generation layer (thickness 50nm) / lithium fluoride (LiF) (thickness 1nm) / aluminum (Al) (thickness 100nm), wherein the structure of the charge generation layer is: a mixture of compound C1 and Li (the mass ratio of C1 to Li is 98:2) (thickness 10nm) / p-dopant (thickness 5nm) / compound L2 (thickness 35nm).
[0101] All devices in this experiment were prepared on a glass substrate with patterned ITO. First, the ITO glass substrate was ultrasonically cleaned 3 times with deionized water and an ultrasonic cleaner for 15 minutes each time. Next, the ITO glass substrate was blown dry with a nitrogen gun and placed in an oven at 120°C for 10 minutes to remove moisture from the surface of the ITO glass substrate. The ITO glass substrate was then placed in a plasma cleaner for 5 minutes to remove tiny particles and organic matter on the surface of the substrate and to improve the work function of ITO. The ITO glass substrate was placed in a vacuum thermal evaporation device to maintain the pressure in the evaporation chamber below 6×10 -5 Pa, according to the above experimental device structure, various functional layers and electrodes were evaporated on the ITO glass substrate in sequence to prepare the experimental device 1.
[0102] Experimental Device 2-18
[0103] The compounds C1 and L2 in the charge generation layer structure of the experimental device 1 were replaced according to the experimental combinations in Table 2 to prepare experimental devices 2-18.
[0104] Comparative experimental devices 1-4
[0105] The compounds C1 and L2 in the charge generation layer structure of the experimental device 1 were replaced according to the comparative combinations in Table 2 to prepare comparative experimental devices 1-4.
[0106] The current density of the packaged experimental device corresponding to the voltage of -7V was tested at room temperature using a digital source meter Keithley 2400. The specific test results are shown in Table 2.
[0107] The magnitude of the current density can reflect the strength of the charge generation ability of the composition. The greater the current density at the same voltage, the more charge the composition generates and the stronger the charge generation ability. When the composition provided by the present invention is used as a charge generation layer in a stacked device, its efficiency is also higher.
[0108] Table 2
[0109]
[0110]
[0111] Note: The mass ratio of compound 1 to compound 2 is 98:2.
[0112] From the data in Table 2, it can be seen that when C1 is used in combination with L3 or L6, C2 is used in combination with L4, and C5 is used in combination with L1 or L2 or L3, the ability of the charge generation layer to generate charges can be significantly improved. At the same time, since the planarity of the fluorene structure is good and the stacking is better than that of biphenyl or benzene + naphthalene substituents, the combination of C3 and L5 and I2 / and L5 does not improve the charge generation ability as significantly as the fluorene structure. For the case where I2 and L3 or the comparative example do not have the same / similar substituents, the charge generation ability is significantly lower.
[0113] Fabrication and characterization of OLEDs
[0114] Device Embodiment
[0115] The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate;
[0116] Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an n-type charge generation layer and a p-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.
[0117] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.
[0118] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably used as the n-type charge generation layer material of the device.
[0119] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The n-type charge generation layer material adopts a deuterated organic compound provided by the benzene invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).
[0120] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:
[0121] Device Example 1
[0122] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr.
[0123] Then, the following operations were performed: first, L2 and p-dopant-1 (the mass ratio of L2 to p-dopant-1 was 97:3) were vacuum deposited on the ITO layer (anode) formed on the substrate with a thickness of 10 nm to form a hole injection layer; secondly, L2 was vacuum deposited on the hole injection layer with a thickness of 20 nm to form a first hole transport layer; secondly, EB-1 was vacuum deposited on the first hole transport layer with a thickness of 5 nm to form a first electron blocking layer; secondly, a mixture of BH-1 and BD-1 was vacuum deposited on the first electron blocking layer with a thickness of 20 nm to form a first light-emitting layer, wherein BH -1 as the host and BD-1 as the dopant, with the mass ratio of the host to the dopant being 98:2; then, on the first light-emitting layer, HB-1 was vacuum deposited with a thickness of 5 nm to form a first hole blocking layer; then, on the first hole blocking layer, ETL-1:LiQ (the mass ratio of ETL-1 to LiQ was 1:1) was vacuum deposited with a thickness of 15 nm to form a first electron transport layer; then, on the first electron transport layer, C1 and Yb (the mass ratio of C1 to Yb was 98:2) were vacuum deposited with a thickness of 15 nm to form an n-type charge generation layer, and L2 and p-dopa were vacuum deposited with a thickness of 10 nm. Then, on the hole generating layer, L2 was vacuum deposited at a thickness of 20 nm to form a second hole transport layer. Then, on the second hole transport layer, EB-1 was vacuum deposited at a thickness of 5 nm to form a second electron blocking layer. Then, on the second electron blocking layer, a mixture of BH-1 and BD-1 was vacuum deposited at a thickness of 20 nm to form a second light-emitting layer, wherein BH-1 was used as a host and BD-1 was used as a dopant, and the mass ratio of the host to the dopant was 98:2. Then, on the second light-emitting layer, 5 HB-1 is vacuum deposited with a thickness of nm to form a second hole blocking layer; then, ETL-1 and LiQ (the mass ratio of ETL-1 to LiQ is 1:1) are vacuum deposited on the above-mentioned second hole blocking layer with a thickness of 15 nm to form a second electron transport layer; then, Yb is deposited with a thickness of 1 nm to form an electron injection layer on the above-mentioned second electron transport layer, and then, Mg and Ag (the mass ratio of Mg and Ag is 1:9) are deposited on the above-mentioned electron injection layer with a thickness of 15 nm to form a cathode, and then, CPL-1 is deposited with a thickness of 50 nm to form a covering layer on the above-mentioned cathode, to prepare a stacked organic electroluminescent device.
[0124] In addition to the materials used in the present invention, the molecular structures of the remaining materials in each layer of the device are as follows:
[0125]
[0126] Device Examples 2-18
[0127] The C1 in the n-type charge generation layer and the L2 in the p-type charge generation layer in Device Example 1 were replaced with the compounds in Table 3, respectively, to obtain Device Examples 2-18.
[0128] Device Comparison Examples 1-4
[0129] The C1 in the n-type charge generation layer and the L2 in the p-type charge generation layer in the device example 1 were replaced with the compounds in Table 3, respectively, to obtain device comparative examples 1-4.
[0130] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 200 mA / cm2, which is calculated as a function of the luminous density from the current / voltage / luminous density characteristic line (IVL characteristic line) showing Lambertian emission characteristics. The lifespan LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 20 mA / cm2 2 The expression L1 = 90% means that at 20 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means, at 20mA / cm 2 When working under this condition, the luminous brightness drops to 95% of its initial value L0 after time LT.
[0131] The data of various OLED devices are summarized in Table 3. Various parameters of the device examples and the device comparative examples are compared to show the performance data of various OLED devices.
[0132] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:
[0133] Quantum efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;
[0134] Current density and lighting voltage: tested using a digital source meter Keithley 2400;
[0135] Blue index is obtained by dividing the quantum efficiency CE (cd / A) by the color coordinate (CIEy);
[0136] Life test: Use LT-96ch life test device.
[0137] Table 3
[0138]
[0139]
[0140] It can be seen from the device test results that the composition provided by the present invention is applied to the n-type charge generation layer and the p-type charge generation layer of the organic electroluminescent device. The composition provided by the present invention can not only significantly improve the ability of the charge generation layer to generate charges, but also improve the π-π stacking effect at the interface between the n-type charge generation layer and the p-type charge generation layer, reduce the injection barrier of the n-type charge generation layer and the p-type charge generation layer and the driving voltage of the device, thereby significantly reducing the device voltage and the power consumption of the overall panel, overcoming the defects of the prior art.
[0141] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A composition for a charge generation layer, characterized in that: The composition comprises a general structure shown in Formula I and a general structure shown in Formula II: N(Ar1)(Ar2)(Ar3)II; In Formula I, R1 and R2 are the same or different, and are independently selected from any one of H, C1-C10 alkyl, and phenyl; Ar is selected from one or more combinations of benzene, spirobifluorene, dibenzofluorene, dimethylfluorene, diphenylfluorene, biphenyl, terphenyl, and naphthalene; In Formula II, Ar1 to Ar3 are the same or different, and each is independently selected from a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted C6-C30 heteroaryl group, and at least one of Ar1 to Ar3 is selected from a combination of one or more of benzene, spirobifluorene, benzophenone, dimethylfluorene, diphenylfluorene, biphenyl, terphenyl, and naphthalene.
2. The composition according to claim 1, characterized in that The Ar is selected from one of the following structures:
3. The composition according to claim 1, characterized in that Ar1 to Ar3 are selected from one of the following structures:
4. The composition according to claim 1, characterized in that R1 and R2 are each independently selected from any one of H, methyl and phenyl.
5. The composition according to claim 1, characterized in that The formula I is selected from one of the structures shown below:
6. The composition according to claim 1, characterized in that The formula II is selected from one of the structures shown below:
7. Use of the composition according to any one of claims 1 to 6 in the preparation of an organic electroluminescent device.
8. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more compositions as described in any one of claims 1 to 6.
9. The organic electroluminescent device according to claim 8, characterized in that: The charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more compounds having a structure shown in Formula I, and the p-type charge generation layer includes one or more compounds having a structure shown in Formula II.
10. A display or lighting device, characterized in that The display or lighting device comprises the organic electroluminescent device according to claim 8 or 9.